Previously unknown evolutionary groups dominate the ssDNA gokushoviruses in oxic and anoxic waters of a coastal marine environment - Labonté, Jessica M.; Hallam, Steven J.; Suttle, Curtis A. (Frontiers in Microbiology, 2015)
Metagenomic studies have revealed that ssDNA phages from the family Microviridae subfamily Gokushovirinae are widespread in aquatic ecosystems. It is hypothesized that gokushoviruses occupy specialized niches, resulting in differences among genotypes traversing water column gradients. Here, we use degenerate primers that amplify a fragment of the gene encoding the major capsid protein to examine the diversity of gokushoviruses in Saanich Inlet, a seasonally anoxic fjord on the coast of Vancouver Island, British Columbia. Amplicon sequencing of samples from the mixed oxic surface (10 m) and deeper anoxic (200 m) layers indicated a diverse assemblage of gokushoviruses, with greater richness at 10 m than 200 m. A comparison of amplicon sequences with sequences selected on the basis of RFLP patterns from eight surface samples collected over a one-year period revealed that gokushovirus diversity was higher in spring and summer during stratification, and lower in fall and winter after deep-water renewal, consistent with seasonal variability within gokushovirus populations. Phylogenetic analysis of clustered amplicons revealed at least five new phylogenetic clades of previously unknown sequences, with the most abundant group associated with viruses that infect SUP05, a ubiquitous and abundant member of marine oxygen minimum zones. Our results provide persuasive evidence that, while specific gokushovirus genotypes may have a narrow host range, hosts for gokushoviruses in Saanich Inlet consist of a wide range of bacterial taxa, including SUP05, a taxonomic clade of gamma proteobacterial sulfur oxidizers. Members of SUP05 are abundant in Saanich Inlet and involved in carbon, nitrogen, and sulfur cycling along the redoxline; thus, gokushoviruses are likely important mortality agents of these bacteria and have consequent influences on biogeochemical cycling in this system.